2005
DOI: 10.1177/0001699305059943
|View full text |Cite
|
Sign up to set email alerts
|

What the Future May Bring

Abstract: The educational system is assumed to facilitate our full participation in society by laying the foundation for participatory rights and possibilities and at the same time strengthening civil society by fostering its individuals into democratic citizens. The question is what the future may bring if continuous economic cutbacks in the educational system lead to diminishing resources for the teaching of values of liberal democracy and multiculturalism. I try to answer this question by focusing on how xenophobia a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 39 publications
0
11
0
1
Order By: Relevance
“…Tolerance is an abstract ideological belief, based on understanding of equalitarian principles (Cote & Erikson, 2009;Rydgren, 2004). Prejudice, on the other hand, is a preconceived stereotype characterized by negative emotional evaluation of an outgroup and does not necessarily reflect abstract reasoning ability (Hjerm, 2005;Pettigrew, 1998). In line with this, the studies of Van Zalk, Zalk, Kerr, and Stattin (2013) as well as Van Zalk and Kerr (2014) showed prejudice and tolerance to be better represented as two related, yet distinct dimensions.…”
Section: Development Of Prejudice and Tolerancementioning
confidence: 92%
“…Tolerance is an abstract ideological belief, based on understanding of equalitarian principles (Cote & Erikson, 2009;Rydgren, 2004). Prejudice, on the other hand, is a preconceived stereotype characterized by negative emotional evaluation of an outgroup and does not necessarily reflect abstract reasoning ability (Hjerm, 2005;Pettigrew, 1998). In line with this, the studies of Van Zalk, Zalk, Kerr, and Stattin (2013) as well as Van Zalk and Kerr (2014) showed prejudice and tolerance to be better represented as two related, yet distinct dimensions.…”
Section: Development Of Prejudice and Tolerancementioning
confidence: 92%
“…In considering cultural factors more broadly, Berry et al (2006) have suggested that substantial perceived cultural differences between natives and immigrants serve as a barrier to positive intercultural relations and, by extension, positive development among immigrant youth. To provide another example, this focus on the magnitude of perceived cultural differences has led researchers in several countries, including the Netherlands, Sweden, and the United States, to focus specifically on relationships involving Muslim youth (Gieling, Thijs, & Verkuyten, 2010;Gonzalez et al, 2008;Hjerm, 2005;Lyons, Kenworthy, & Popan, 2010).…”
Section: Diversity Of Immigrant Groupsmentioning
confidence: 99%
“…Current research is limited in its generalizability, however, as samples have typically been drawn from countries with longer histories of democracy that are also more likely to be what are called "immigrant-receiving," as opposed to "immigrant sending" (e.g., Brown, 2011, in the United States;Bratt, 2005;Hjerm, 2005;and Snellman & Ekehammar, 2005, in the Nordic countries; Malti, Killen, & Gasser, 2011, in Switzerland;Nesdale, 2008, in Australia;and Verkuyten & Steenhuis, 2005, in the Netherlands). However, perhaps as a result of the limited contexts studied, larger social factors, or policies framing attitude development among young people are rarely considered.…”
mentioning
confidence: 99%
“…This study follows the line of thinking that emphasizes that positive and negative sentiments toward immigrants should be understood as separate dimensions (Van Zalk et al, 2013). This is because, whereas positive sentiments toward immigrants derive from abstract, prodemocratic considerations of equality, inclusion, and empathetic concerns, anti-immigrant sentiments, by contrast, stem from perceptions of difference that are rooted in fear (Hjerm, 2005;Paluck & Green, 2009). Empirically, cross-sectional studies have shown that adolescent-peer similarities in sentiments toward immigrants (Kuhn, 2004) and also peer network diversity are important for developing positive sentiments toward immigrants (Côté & Erickson, 2009;Harell, 2010).…”
Section: Peer Influence and Selectionmentioning
confidence: 80%
“…This rise in intolerance has led to a harsher political climate. Irrespective of position on the ideological left-right continuum, inflexible ideological opinions have gone hand-in-hand with violent and illegal political confrontations and protests (Flyghed, 2013;Hjerm, 2005). Given that the teenage years are a period when influences from peers seem to peak (Berndt, 1982;Buhrmester & Furman, 1987), adolescence is a suitable period for examining: 1) the role of peers in adolescents' development of universalistic values and positive immigrant sentiments and, 2) the extent to which influences from a more universalistic and immigrant-friendly network of peers can reduce adolescents' approval of violent political means.…”
Section: Introductionmentioning
confidence: 99%